ANTI-CORRUPTION ACTIVITIES OF THE STATE: THEORETICAL ASPECTS - Gryn, I. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
A phenomenon of corruption is considered. The sources, social content, features of corruption and corruption aspects are determined. The factors of corruption, its development in the state are analyzed. Anticorruption activity in Ukraine and its influence on the present are considered. A conceptual-categorical apparatus used for studying corruption is explored and specified. The influence of corruption and corrupt acts on the state policy is determined. The special preconditions of corruption and strategies of struggle with them are analyzed.